Electronic stethoscope - Retnam, Parameswary (2006)
The stethoscope is one of the most simple and practical diagnostic tools used in medicine. Presently, two different types of stethoscopes available on the market are acoustic and electronic. Advantages of acoustic stethosco p e are overcome by the sensitivity of the electronic stethosco p e to manipulation artifacts,and electronic and ambient noises. Also, they do not take into consideration the sensitivity of the human ear, which varies significantl y as a function of frequency. Therefore electronic stethoscope has become the demand in this new era of technology. The purpose of this project is to desi g n an amplifier circuit which is used in electronic stethoscope (biomedical instrumentation). This project is focusing mainly on the operational amplifier which is used for multiple purposes. Basically the whole process is trying to amplify a small signal into a larger signal with reduced noise so that the output signal will he greatly amplified. Operational am plifier is used for the purnose of am plif y in g the output signal. The output will he displayed in an oscilloscop e to see the amplified signal. The designed circuit will be first simulated by usin g the OR-CAD software to analyze the output of the signal processing throu g hout each of the op-amp; Subsequently, we have to desi gn the hardware of the circuit to design a functional circuit which is reliable with thç theory . The expected out p ut/results are an amplified signal with reduced noise.